Prospective randomized trial with Palonosetron verses ondensetron for postoperative nausea and vomitting in general surgical population - Meenal Agarwal; Nazeer Ahmed K; Rajendra Kumar; M.M. Watwe; Manjari Deshpande; Sameena Kausar; Mubeena Begum (Al Ameen Medical College, 2016)
Background: Postoperative nausea and vomiting (PONV) is distressing complication of anesthesia and surgery. It has been suggested that this may increase patients' discomfort, increase costs and other unwarranted side effects and complications. Aim and objectives: To study incidence of PONV, in Indian scenario and association of PONV with various factors and efficacy of palonosetron verses ondensetron in this prospective randomized control trial. Materials and Methods: Prospectively preoperative and ICU - related data of 170 patients, who underwent laparoscopic surgical procedures under general anesthesia, were collected. Preoperative variables included age, sex, obesity, history of diabetes, and previous PONV and/or motion sickness. ICU - related data included number of episodes of PONV, need for rescue medication, and QTc interval procedures. Patients were extubated after surgery and were shifted to either ICU or wards for further post operative care. Patients who developed PONV were randomized by computer generated random number table to receive intravenous injection palonosetron 0.075mg or injection ondensetron 4 mg. Results: Out of 170 patients, PONV was documented in 52 i.e. 30.50 % of cases. Previous history of PONV, diabetic status, female sex and opiod was found to be significantly associated with PONV with p values of 0.042, 0.0513, 0.002, and 0.0038 respectively. Among 52 cases of PONV, after randomization 27 patients received palonosetron while 25 received Ondensetron. Successful treatment from PONV was observed in 26 cases of palonosetron while 22 cases of ondensetron. This difference did not culminate into statistically significant levels with p value of 0.3499 indicating both drugs were similar in efficacy for PONV. Conclusion: Data on PONV in general surgical patients is limited in Indian scenario with the incidence is as high as around 30%. Incidence of PONV is high with risk factors like female sex, diabetic status,use of opiods and previous history of PONV. Newer 5HT3 antagonist palonosetron is equally effective for PONV treatment as ondensetron.